Retention, stability, iron bioavailability and sensory evaluation of extruded rice fortified with iron, folic acid and vitamin B12 - Jyrwa, Yvette Wilda; Palika, Ravindranadh; Boddula, Swetha; Boiroju, Naveen Kumar; Madhari, Radhika; Pullakhandam, Raghu; Thingnganing, Longvah (Maternal and child nutrition, 2020)
Fortification of rice with micronutrients using extrusion technology is considered a sustainable strategy to prevent nutritional deficiencies in general population. The objective of the present study is to assess the retention, stability and iron bioavailability from indigenously developed triple fortified rice (iron, folic acid and vitamin B12) during rinsing and different cooking methods. Further, we also assessed the acceptability of fortified rice in adult human volunteers. The retention of iron during rinsing with excess water was ≥90%, whereas folic acid and vitamin B12 levels were reduced by ~25% during rinsing. Watertight cooking of rice (in electric cooker or on flame) had no additional effect on the nutrient levels as compared with rinsed rice, implying their stability during cooking. However, cooking with excess water followed by decanting led to loss of 45% iron and ≥70% folic acid and vitamin B12. The dialyzable iron and ferritin synthesis in Caco‐2 cells was significantly (P < .01) higher from fortified rice compared with unfortified rice. In addition, inclusion of ascorbic acid significantly (P < .01) increased the iron bioavailability from the fortified rice. Triangle tests in adult human subjects revealed that there are no significant sensory differences among fortified and unfortified rice. Further, fortified rice consumption appears to bridge the gaps in dietary iron intake deficits in children and women of reproductive age. These results suggest that the iron‐, folic acid‐ and vitamin B12‐fortified rice has higher retention and stability of fortified nutrients and is acceptable for consumption in adult human volunteers.